2017
DOI: 10.5797/jnet.cr.2016-0123
|View full text |Cite
|
Sign up to set email alerts
|

A Case of Acute Embolic Occlusion of the Brachiocephalic Artery Recanalized with Endovascular Thrombectomy

Abstract: Objective: Endovascular treatment of a patient with acute embolism of the brachiocephalic artery (BCA) is reported. Case Presentations:A 70-year-old woman presenting with weakness of the right upper extremity was transferred to our hospital due to acute embolism of the BCA. After the right brachial artery was secured by direct cardiovascular surgery, a balloon guidewire was inserted through the femoral artery and advanced near the thrombus in the BCA, and the balloon at its tip was inflated in the right intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The time from the onset to reperfusion is one of the strongest predictors of the outcome in patients with LVO (10). Recently, the direct transfer to angiosuite (DTAS) protocol for patients suspected of having LVO based on a scoring system of acute stroke code, such as the Rapid Arterial oCclusion Evaluation (RACE) scale, was reported to be useful for shortening the time from admission to revascularization and improving the outcome (11,12) However, Pfaff et al reported that there was no significant difference in the door-to-reperfusion time between the DTAS group and the conventional workflow group (13,14). These results suggest that the reduction in in-hospital delays depends on the capability and availability of the angiosuite at the time of admission and the feasibility of a floor plan for treating AIS patients.…”
Section: Discussionmentioning
confidence: 99%
“…The time from the onset to reperfusion is one of the strongest predictors of the outcome in patients with LVO (10). Recently, the direct transfer to angiosuite (DTAS) protocol for patients suspected of having LVO based on a scoring system of acute stroke code, such as the Rapid Arterial oCclusion Evaluation (RACE) scale, was reported to be useful for shortening the time from admission to revascularization and improving the outcome (11,12) However, Pfaff et al reported that there was no significant difference in the door-to-reperfusion time between the DTAS group and the conventional workflow group (13,14). These results suggest that the reduction in in-hospital delays depends on the capability and availability of the angiosuite at the time of admission and the feasibility of a floor plan for treating AIS patients.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusive endovascular treatment can sometimes be achieved by excluding the thrombus with the use of covered stents through a carotid cutdown with CCA control. Exclusive use of thrombectomy/aspiration catheters has also been described 17 ; however, it requires the use of multiple embolic protection devices (EPDs), making it cumbersome and at risk of embolism if the guidewire is pushed through the clot antegrade to place the EPD, so we consider this management a high-risk approach.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusive endovascular treatment can sometimes be achieved by excluding the thrombus with the use of covered stents through a carotid cutdown with CCA control. Exclusive use of thrombectomy/aspiration catheters has also been described 17 ; however, it requires the use of multiple embolic protection devices (EPDs), making it cumbersome and at risk of embolism if the guidewire is pushed through the clot antegrade to place the EPD, so we consider this management a high-risk approach. Given that the IA is a large diameter (15-16 mm) and short artery, 18 it is not uncommon to lack a suitable stent-graft to cover arteries larger than 16 mm; in that case, treatment of the IA thrombus can be achieved by a hybrid procedure, excluding the thrombus with off-label use of widely available iliac extension stent-grafts and right subclavian artery revascularization when its origin is occluded by the stent-graft.…”
Section: Discussionmentioning
confidence: 99%
“…Surgery or hybrid treatment consisting of surgery and endovascular treatment has been reported. [2][3][4] In this study, we report a patient in whom thrombectomy for a giant thrombus in the CCA using the parallel stent retriever technique with two Solitaire (Medtronic, Minneapolis, MN, USA) devices led to complete recanalization.…”
Section: Introductionmentioning
confidence: 97%
“…Surgery or hybrid treatment consisting of surgery and endovascular treatment has been reported. 2 4) …”
Section: Introductionmentioning
confidence: 99%